Isolation of antioxidative compounds from Micromelum minutum guided by preparative thin layer chromatography-2,2-diphenyl-1-picrylhydrazyl (PTLC-DPPH) bioautography method - Kassim, Nur Kartinee; Lim, Pei Cee; Ismail, Amin; Awang, Khalijah (Elsevier, 2019)
The application of preparative thin layer chromatography-2,2-diphenyl-1-picrylhydrazyl (PTLC-DPPH) bioautography technique successfully isolated a lignan sesamin (1), two prenylated coumarins (2 and 3) and a marmesin glycosides (4) from Micromelum minutum methanol bark extract. Compounds 2 and 3 were identified as new compounds whereas 1 and 4 were first isolated from Micromelum genus. Structural identification of all compounds were done by detailed spectroscopic analyses and comparison with literature data. Antioxidant capacities of extract, active fraction and compounds were measured based on DPPH free radical savenging activity, oxygen radical absorbance capacity (ORAC) and β-carotene bleaching. The DPPH activity of methanol extract and its fraction present the IC50 values of 54.3 and 168.9 µg/mL meanwhile the β-carotene bleaching results were 55.19% and 5.75% respectively. The ORAC measurements of M. minutum extract, compounds 2 and 4 showed potent antioxidant activity with the values of 5123, 5539 and 4031 µmol TE/g respectively.